Iterative frequency-domain receivers for the uplink of cellular systems with base station cooperation - Ribeiro, F.
In this paper we consider the uplink transmission in BS (Base Station) cooperation schemes where users in adjacent cells share the same physical channel and the signals received by each BS are sent to a CPU (Central Processing Unit) that combines the different received signals associated to a given user and/or performs the user separation. We consider SC-FDE signals (Single-Carrier with Frequency-Domain Equalization) combined with iterative frequency-domain receivers based on the IB-DFE concept (Iterative Block Decision Feedback Equalization). Our performance results show that the proposed receivers allow significant macro-diversity gains as well as an efficient user separation, with performance close to the MFB (Matched Filter Bound), making these techniques an excellent choice for the uplink transmission in future broadband wireless systems employing BS cooperation schemes.